1997
DOI: 10.1177/01454455970211006
|View full text |Cite
|
Sign up to set email alerts
|

Pain Behavior, Spouse Responsiveness, and Marital Satisfaction in Patients with Rheumatoid Arthritis

Abstract: Although the pain behavior of some diagnostic groups has been shown to be reactive to social influences, the reactivity of pain behavior in a rheumatoid arthritis (RA) population remains an open question. The authors in this article combined laboratory and self-report assessment techniques to examine the extent to which the pain report and behavior of 52 RA patients was susceptible to influence of social factors within the marital unit. The authors' findings suggest that (a) different types of spouse responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…Previous studies have shown that marital satisfaction reflects a complex set of interactions between partners and can also be influenced by the physical health of the spouses (20). Therefore, we hypothesized that both coping styles and disease activity would be associated with marital satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that marital satisfaction reflects a complex set of interactions between partners and can also be influenced by the physical health of the spouses (20). Therefore, we hypothesized that both coping styles and disease activity would be associated with marital satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…29 Another research team found that solicitous spouse responses were positively associated with pain interference. 102 Lousberg et al 50 found that ICPs' perceptions of spouse solicitous responses were not related to walking time or exertion measured by heart rate; however, spouses' reports of their solicitous responses were significantly and positively related to ICPs' activity limitations. Researchers have found that marital satisfaction moderated the relationship between disability and solicitous spouse responses such that ICPs who are maritally satisfied exhibited a stronger relationship between solicitous spouse responses and disability than ICPs who are not as satisfied within their marriage.…”
Section: Physical Disability and Activity Limitationsmentioning
confidence: 99%
“…Further, the literature reports that patients perceive greater punishing respsonses than spouses perceive, or that there are no mean differences in perceptions of punishing responses (Cano et al, 2004b;Williamson et al, 1997). No differences between patient and spouse perceptions of distracting responses have been found (Williamson et al, 1997).…”
Section: Agreement On Spouse Responses To Painmentioning
confidence: 99%
“…Researchers have found that patients perceive fewer spouse solicitous responses or that there are no patient-spouse differences in perceptions of solicitousness (Cano et al, 2004b;Lousberg et al, 1992;Williamson et al, 1997). Further, the literature reports that patients perceive greater punishing respsonses than spouses perceive, or that there are no mean differences in perceptions of punishing responses (Cano et al, 2004b;Williamson et al, 1997).…”
Section: Agreement On Spouse Responses To Painmentioning
confidence: 99%